Pengelolaan Limbah Industri Kimia untuk Keberlanjutan Lingkungan di Indonesia - Putri, Hani Helmalia; Syafira, Fairuz Tri Septiani (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research analyzes the management of chemical industrial waste in Indonesia which plays a crucial role in efforts to achieve environmental sustainability in line with the growth of the industrial sector. The research is descriptive qualitative in nature and includes library research (library study), where the data used is secondary data which includes books, journals and websites that are related to this research. The data obtained is then processed, analyzed and concluded. The results of this research found that sustainable management of chemical industrial waste in Indonesia requires the active participation of all stakeholders, encouraging sustainable solutions, supporting responsible economic growth, and preserving the environment for a sustainable future. Good synergy between government, industry and society is the key to achieving holistic sustainability goals.